Inclusive Japanese Language Use In Support Of Gender Equality - Satriatama, Prasetya Eghy (KIRYOKU, 2024)
Gender-differentiated language use in Japanese stems from traditions and social norms that have developed over time. However, usage  of gender-neutral Japanese is still not very popular in Japan. This article aims to provide an insight into gendered language use, particularly gender-based language use. The method used to write this article is a qualitative approach with an analytical descriptive method. The data is then collected through literature study. Also, the data sources used in this study are books, journals, articles and online news related to the uses of neutral Japanese in Japanese society. In this article, the author analyzes the data obtained from the book "Queer Japanese: Gender and Sexual Identities through Linguistic Practices" by Hideko Abe published in 2010 and “Japanese Language and Gender: An Introduction" by Kadek Eva Krishna Adnyani published in 2019. Based on these two books, it can be concluded that the use of gender-neutral language in Japanese is crucial in creating gender equality and inclusivity for all individuals regardless of their gender. However, language change is not the only solution to creating gender equality. There needs to be a broader effort in changing mindsets and social norms that are not inclusive and respectful of gender diversity.